Edublogs: a Media to Improve Students’ Writing Skill in Recount Text - Riswandi, Diki; Ngadiso, N; Asib, Abdul (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
This study designed to improve students’ writing skills through Edublogs of one Senior High Schools in Indonesia. Based on the preliminary observation, there were problems found in the field such as students’ poor writing skills and low interest toward writing, inappropriate teacher’s style in teaching, the role of media and the unsuitable utilization of internet facility. Regarding to the result of the observations, students had some problems in recount text writing those are the generic structure, the purpose and the language features. In addition, they had no capability to make a self-reflection on their mistakes in their own writing. It happens since their English teacher has a tendency to to directly correct their mistakes.This current research was an action research study consisting of two cycles. There are 23 students involved in this study. The data of this study were qualitative and quantitative. The qualitative data were obtained, the first, by observing the teaching and learning process during the implementation of the actions and the second, by interviewing the students and the collaborator about the actions implemented. Furthermore, the qualitative data were in the form of field notes and interview transcripts. Meanwhile, the quantitative data were gained by assessing the students’ writing skills through the pretest and posttest. The qualitative data were analyzed using the qualitative data analysis those are data collection, data reduction, data display, and conclusion drawing and verification. The results of this study show that Edublogs is an effective media that can be used to improve students’ writing skills qualitatively and quantitatively. Qualitatively, using Edublogs, teaching and learning process became more interesting. The students enjoyed the writing process. The students’ problems in writing can be reduced by using Edublogs in teaching-learning process by applying writing stages through Edublogs. Quantitatively, the average score gained by the students in cycle one was 67.37 while in cycle two is 72.58. The results, however, show that students’ writing skill improves significantly through blogging activity. Thus, it can be concluded that the students are more enthusiastic and more interested in writing English.